2017
DOI: 10.1093/biolre/iox032
|View full text |Cite
|
Sign up to set email alerts
|

The gonadotropin-inhibitory hormone (Lpxrfa) system's regulation of reproduction in the brain–pituitary axis of the zebrafish (Danio rerio)†

Abstract: Gonadotropin-inhibitory hormone (GNIH) was discovered in quail with the ability to reduce gonadotropin expression/secretion in the pituitary. There have been few studies on GNIH orthologs in teleosts (LPXRFamide (Lpxrfa) peptides), which have provided inconsistent results. Therefore, the goal of this study was to determine the roles and modes of action by which Lpxrfa exerts its functions in the brain-pituitary axis of zebrafish (Danio rerio). We localized Lpxrfa soma to the ventral hypothalamus, with fibers e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 42 publications
4
41
0
Order By: Relevance
“…These results are supported by previous studies showing the presence of RFamide peptides in the NOR or nervus terminalis, where they co‐localise with GnRH, although not completely in some species . Recently, Spicer et al . demonstrated the lack of co‐localisation of GnIH and GnRH3, and the absence of a GnIH‐IR cell cluster in the nervus teminalis of Danio rerio , after using a specific antiserum raised against zebrafish‐LPXRFa .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results are supported by previous studies showing the presence of RFamide peptides in the NOR or nervus terminalis, where they co‐localise with GnRH, although not completely in some species . Recently, Spicer et al . demonstrated the lack of co‐localisation of GnIH and GnRH3, and the absence of a GnIH‐IR cell cluster in the nervus teminalis of Danio rerio , after using a specific antiserum raised against zebrafish‐LPXRFa .…”
Section: Discussionsupporting
confidence: 82%
“…Although GnIH was first characterised in this group in 2002, knowledge of its role increased only recently. Most studies focused on the reproductive function of GnIH and reported both stimulatory and inhibitory effects of the hormone . This dual effect has been proposed to depend on the action of sex‐steroids and neuro‐oestrogens and on the abundance of GnIH, GnRH and oestrogen receptors in the plasmatic membrane …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of GnIH:GnRH actions in the fish brain have been particularly informative. In zebrafish ( Danio rerio ), an elegant study on the GnIH orthologue (LPXRFamide, or LPXRFa) demonstrated that, in the preoptic area, LPXRFa fibres interact with gonadotrophin‐releasing hormone 3 (GnRH3) cell bodies and LPXRFa‐3 reduced GnRH3 expression in brain slices . Furthermore, zebrafish LPXRFa‐2 and LPXRFa‐3 antagonises kisspeptin‐2 (Kiss2) activation of kisspeptin receptor‐1a (Kiss1ra) and kiss1ra‐expressing neurones in the preoptic area are innervated by LPXRFa‐immunoreactive (‐ir) fibres; an overview of teleost kisspeptin is provided elsewhere .…”
Section: Commonalities and Diversity Of Gnih/rfrp‐3mentioning
confidence: 99%
“…The GnIH homologue in teleost fish, LPXRF, acts on the anterior pituitary gland across species. In pituitary explants of zebrafish, LPXRFa‐3 down‐regulates LHβ subunit and gonadotrophin common α subunit expression . In tilapia, the actions of GnIH on the anterior pituitary are likely more widespread, with LPXRFa‐receptor expressed in LH, adrenocorticotrophin‐releasing hormone and α‐melanocyte‐stimulating hormone cells, and LPXRFa in this species appears to be a positive regulator of reproduction …”
Section: Commonalities and Diversity Of Gnih/rfrp‐3mentioning
confidence: 99%